Improving Normative and Adaptive Teacher Skills in Teaching PKWU Subjects: Peningkatan Keterampilan Guru Normatif dan Adaptif dalam Mengampu Mata Pelajaran PKWU - Dedi Darwis; A. Ferico Octaviansyah Pasaribu; Sampurna Dadi Riskiono (Yayasan Ahmar Cendekia Indonesia, 2020)
Based on the existing guidelines in the 2013 revised curriculum, Creative Products and Entrepreneurship (PKWU) subjects have changed for the number of hours of lessons, namely currently there are six lesson hours for one week, while for adaptive and normative subjects the number of lessons has decreased. However, the teachers at SMK YPI generally do not have dual competencies that can support skills in teaching PKWU subjects. Therefore, training and mentoring are needed as provisions for teachers in teaching PKWU subjects so that the competence and skills of teachers who teach adaptive and normative subjects can increase. The main problem with partners is that the craft program has not been implemented because there is still a need for skills material to be given to students related to entrepreneurship. This service activity is carried out by providing training to normative and adaptive teachers to teach PKWU with materials, namely graphic design and making Bluetooth Mini Amplifier. From the results of the activities carried out, an evaluation was obtained, namely that for an understanding of the PKWU subject, 100% of his knowledge increased. For the use of graphic design applications and their application after training activities, it shows that 85.71% of normative and adaptive teachers know how to use graphic design applications and 14.29% really know and understand the use of graphic design applications. As for the knowledge about making bluetooth mini amplifiers a number of 14.29% of normative and adaptive teachers know enough and 85.71% of normative and adaptive teachers know how to make bluetooth mini amplifiers.